Gradient coating of extracellular matrix derived from endothelial cells on aligned PCL nanofibers for rapid endothelialization - Zhou, Ziyi; Lin, Yijing; Liu, Na; Zhang, Yiming; Li, Bing; Wang, Yuanfei (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionArtificial vascular scaffolds can mimic the structure of natural blood vessels and replace the damaged vessels by implanting them at the injury site to perform the corresponding functions. Electrospinning technology can perfectly combine biological signals and topographical cues to synergistically induce directed cell migration and growth.MethodsIn this study, poly (caprolactone) (PCL) nanofibers, PCL nanofibers uniformly coated with the extracellular matrix derived from endothelial cells (ECd), and bi-directional linear gradient ECd-coated PCL nanofibers were prepared by electrospinning and electrospray techniques to evaluate their effects on the proliferation and migration of Human umbilical vein endothelial cells (HUVECs) and rapid endothelialization.ResultsThe results showed that HUVECs could successfully adhere to the surface of these three nanofibers and maintain high viability. The migration results indicated that the bidirectional linear gradient coating could accelerate the migration of HUVECs and the endothelialization process. On this basis, three types of bionic vascular scaffolds, including PCL vascular scaffold, uniform ECd-coated PCL vascular scaffold, and bi-directional linear gradient ECd-coated PCL vascular scaffold, were further prepared. The results showed that the topology and biological signal of the bi-directional linear gradient ECd-coated PCL vascular scaffold synergistically promoted the migration of HUVECs more effectively.DiscussionThis provides a new way to clinically promote the structural and functional recovery of damaged vessels and develop personalized or universal artificial vascular scaffolds, which is of great importance in cardiovascular regenerative medicine.